Start small. Do it well. Then expand your offerings. - BANSAL, Binny (Institutional Knowledge at Singapore Management University, 2021)
An interview with Binny Bansal. Binny Bansal, co-founder of Flipkart, and co-founder and executive chairman of xto10x, talks about his entrepreneurial journey in the world of e-commerce.